Delayed gait recovery with recovery of an injured corticoreticulospinal tract in a chronic hemiparetic patient: A case report. Issue 46 (November 2016) - Jang, Sung Ho; Kwon, Hyeok Gyu
Abstract: Objectives: We report on a chronic hemiparetic patient whose gait recovery was delayed until healing of an injured corticoreticulospinal tract (CRT), which was demonstrated on diffusion tensor tractography (DTT). Case presentation: A 71-year-old female presented with complete paralysis of the right extremities resulting from a spontaneous intracerebral hemorrhage. At 5 months after onset, when she was admitted for rehabilitation after undergoing rehabilitation at the previous university hospital, she presented with severe weakness of the right leg (manual muscle test: 0 ∼ 2- score) and could not even stand. She received comprehensive rehabilitative therapy for 32 months after the onset. Motor weakness of her right leg improved to the point that she was able to extend her knee on gravity-eliminated position at 11 months and against some resistance at 30 months after onset. She was able to walk independently at 30 months after onset. Results: The left CRT was discontinuous at the basal ganglia level on 5-month DTT. This discontinuation elongated to the cerebral cortex on 32-month DTT, whereas on 32-month DTT, the right CRT had become thicker compared with that on 5-month DTT. Conclusions: An injured CRT healed in a patient who was able to walk independently after approximately 2 years of rehabilitation starting 5 months after the onset of intracerebral hemorrhage.